Chang and Eng Reconnected : the Original Siamese Twins in American Literature and Culture. - Wu, Cynthia, 1973- (Temple University Press, 2012)
Conjoined twins Chang and Eng Bunker have fascinated the world since the nineteenth century. In her captivating book, Chang and Eng Reconnected, Cynthia Wu traces the "Original Siamese Twins" through the terrain of American culture, showing how their inseparability underscored tensions between individuality and collectivity in the American popular imagination. Using letters, medical documents and exhibits, literature, art, film, and family lore, Wu provides a trans-historical analysis that presents the Bunkers as both a material presence and as metaphor. She also shows ho.